2020
DOI: 10.1136/jitc-2020-001487
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic CD8αβ co-receptor rescues endogenous TCR function in TCR-transgenic virus-specific T cells

Abstract: BackgroundGenetically engineered virus-specific T cells (VSTs) are a platform for adoptive cell therapy after allogeneic hematopoietic stem cell transplantation. However, redirection to a tumor-associated antigen by the introduction of a transgenic T-cell receptor (TCR) reduces anti-viral activity, thereby impeding the possibility of preventing or treating two distinct complications—malignant relapse and viral infection—with a single cell therapy product. Availability of CD8αβ co-receptor molecules can signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…For broader applicability of such multi-antigen targeted therapies, the complexity of the production processes needs to be reduced (recently reviewed in (10)). Here, we investigated at small scale if Interferon-g (IFN-g) cytokine capture (CC) selected virus-specific memory T cells from healthy donors are sufficiently enriched and activated to directly proceed to retroviral transduction introducing an HLA-A*02:01 restricted survivin targeted TCR (11) in combination with CD8ab (TCR8) to redirect VSTs to a broad tumor-associated antigen (12,13). We have previously demonstrated that the incorporation of CD8ab as a transgene restores anti-viral activity of TCR transgenic VSTs, and redirects CD4+ T cells to the class I restricted cognate antigen (12,13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For broader applicability of such multi-antigen targeted therapies, the complexity of the production processes needs to be reduced (recently reviewed in (10)). Here, we investigated at small scale if Interferon-g (IFN-g) cytokine capture (CC) selected virus-specific memory T cells from healthy donors are sufficiently enriched and activated to directly proceed to retroviral transduction introducing an HLA-A*02:01 restricted survivin targeted TCR (11) in combination with CD8ab (TCR8) to redirect VSTs to a broad tumor-associated antigen (12,13). We have previously demonstrated that the incorporation of CD8ab as a transgene restores anti-viral activity of TCR transgenic VSTs, and redirects CD4+ T cells to the class I restricted cognate antigen (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we investigated at small scale if Interferon-g (IFN-g) cytokine capture (CC) selected virus-specific memory T cells from healthy donors are sufficiently enriched and activated to directly proceed to retroviral transduction introducing an HLA-A*02:01 restricted survivin targeted TCR (11) in combination with CD8ab (TCR8) to redirect VSTs to a broad tumor-associated antigen (12,13). We have previously demonstrated that the incorporation of CD8ab as a transgene restores anti-viral activity of TCR transgenic VSTs, and redirects CD4+ T cells to the class I restricted cognate antigen (12,13). CC is attractive because it is compatible with fully closed production of VSTs independently of donor HLA and can select T cells with diverse TCR repertoires recognizing various immunogenic epitopes (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Vγ9Vδ2TCR ( 30 ) and CD8αβ-independent αβTCRs ( 32 ) have been also reported to reprogram CD4 + T cells, which not only have the ability to exert tumor cell killing but also induce maturation of professional antigen-presenting cells. Transfer of CD8αβ in combination with intermediate affinity tumor reactive αβTCR has been reported to support tumor control in vitro and in vivo ( 49 , 50 ), and for high affinity αβTCR with artificial signaling domains adding CD8α alone has been shown to reprogram CD4 + T cells ( 36 ). Within this context, our data show that CD8αα in combination with a natural γδTCR serves as costimulatory receptor, as opposed to the well-described inhibitory function of CD8αα on αβT cells within the context of a natural αβTCR.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of CD8αβ to the transgenic TCR vector has been used to rescue endogenous MHC class I-restricted anti-viral TCR function [ 192 , 193 ]. These TCR-transgenic VSTs have a predominant central-memory phenotype and their anti-viral reactivity is preserved together with their anti-tumor function [ 194 ]. The insertion of the CD8αβ co-receptor also improved antigen recognition by the TCR/MHC complex, recruitment of the tyrosine kinase Lck to the immune synapse, and proper activation of signaling components for T-cell activation, in addition to allowing CD4 + T cells to recognize MHC class I-restricted antigens [ 195 , 196 ].…”
Section: Biology Meets Therapy: T-cell Dysfunction In Adoptive Celmentioning
confidence: 99%